ASSOCIATION BETWEEN WHITE BLOOD CELL COUNT AND LEVELS OF SERUM HOMOCYSTEINE IN END-STAGE RENAL FAILURE PATIENTS TREATING WITH HEMODIALYSIS - Bradran, Azar; Nasri, Hamid (Journal of Ayub Medical College Abbottabad, 2006)
Background: In hemodialysis patients, plasma levels of total homocysteine are influenced by nutritional status in patients with chronic kidney disease .To investigate the association between serum homocysteine (Hcy) level as a marker of nutritional status and WBC counts as a marker of inflammation, a cross-sectional study was conducted on patients with end-stage renal disease (ESRD), who were undergoing maintenance hemodialysis treatment. Methods: Serum homocysteine (total) and WBC count were measured. Other biochemical analysis including serum predialysis creatinine (Creat), post and predialysis blood urea nitrogen (BUN), albumin (Alb), serum C-reactive protein (CRP) and serum ferritin were measured, also intact serum PTH (iPTH) and plasma HCO3 was measured too. For the efficacy of hemodialysis the urea reduction rate (URR) was calculated from pre- and post-blood urea nitrogen (BUN) data. The body mass index (BMI) was also calculated. For correlations the partial correlation test was used. Results: Total patients were 36(f=15 m=21), consisting of 25non-diabetic HD patients and 11diabetic HD patients. The mean patient's age was 47±17years. In all patients a significant inverse correlation of serum homocysteine with WBC count and a significant positive correlation of serum Homocysteine with BMI and a near significant positive correlation of WBC count with serum CRP were found. Conclusion: In hemodialysis patients an inverse correlation between WBC count as a marker of inflammation with serum Hcy level as a marker of nutritional status, further support the hypothesis of the malnutrition-inflammation cachexia syndrome Keywords: White blood cell, Serum homocysteine